In-silico and in-vitro Antibacterial Activity and GC-MS Analysis of Anogeissus acuminata Leaf Extract with Host Toxicity Testing (Bangladesh Journal of Infectious Diseases, 2025)
Background: Anogeissus acuminata leaf extract is utilized in the different purposes.Objective: Antibacterial activity of organic solvent fractions of crude leaf extract of Anogeissus acuminata was used against multidrug-resistant strains of 9 pathogenic bacteria isolated from urine samples of patients with urinary tract infections.Methodology: The n-butanol fraction revealed effective control over pathogens, and the zone size was 21 mm as a measure of antibacterial activity against Proteus mirabilis. The gas chromatography-mass spectroscopy analysis indicated the presence of 15 phyto-compounds with docking score values -5 to -7 kcal/mol in a molecular docking attempt against β-lactamase of Pseudomonas aeruginosa.Results: The isolated chemicals, conocarpan and dihydrodehydrodiconiferyl alcohol, had comparatively effective docking scores, -10.908 and -10.081 kcal/mol, respectively. In toxicity testing, the experimental minimum inhibitory concentration value was 600 mg/L, and the computed lethal concentration25 value was 1698.24 mg/L during cytotoxicity assay; it was observed that comet was not found in the cells treated leaf extract.Conclusion: The isolated compounds conocarpan and dihydrodehydrodiconiferyl alcohol achieved successful docking scores against -lactamase in the molecular docking attempt. When the leaf extract was seen using lymphocytes grown from UCB, it was determined that it had no host toxicity.Bangladesh Journal of Infectious Diseases, December 2024;11(2):93-101